The Importance of Feedback and Satisfaction of Stakeholders and Alumni of the Political Science Department of the Faculty of Social Sciences and Politics at UNTL - Por Henrique Cesário da Costa; Martinho Martins; Abrão dos Santos; Saturlino Esteves; Franquelino Freitas (International Journal Labs, 2026)
The evaluation of higher education quality involves active participation from alumni and employers. For the Department of Political Science at the Faculty of Social and Political Sciences (FCSP) of the National University of East Timor (UNTL), understanding how these groups perceive the relevance of courses, the quality of training, and its application in the labor market is crucial. This initiative aims to strengthen institutional evaluation culture and inform strategic decisions to improve training offerings. The study investigates the satisfaction and feedback from alumni and stakeholders in Aileu, Baucau, Ermera, Manatuto, and Liquiça regarding the relevance, function, and sustainability of the Political Science Department. The research emphasizes a participatory approach, involving those who have undergone training and those who interact with graduates professionally. By collecting feedback from alumni and employers, the study aims to gather information to enhance teaching quality and course relevance, thereby contributing to social and institutional recognition. A qualitative, descriptive approach (Moleong, 2017) was used, including semi-structured interviews with alumni and stakeholders in the target municipalities. The study finds that most alumni (93%) work in the public sector, with only a small percentage in the private sector. Regarding course evaluation, 93% of alumni felt the training contributed significantly to their professional performance. Employers also evaluated the alumni positively, highlighting their adaptability and rule compliance. Recommendations include improving infrastructure, offering continuous education events, and ensuring the course's continued relevance to the labor market, especially in public and private sectors. Employers also advocate for enhanced political science education to prepare future leaders.